Optimization of the Continuing Professional Development Program (PKB) as a Follow-up to Online Competency Mapping (PK) for Islamic Religious Education Teachers - Supratama, Riky; Kholifah, Elisa Putri; Ramadani, Mega Melani; helwiyah, Warda (Yayasan Azhar Amanaa Yogyakarta, 2024)
The first government initiative to improve the competency of PAI teachers was the Professional Development Program (PKB). This program is said to be able to improve the quality of PAI teachers' work when conducting online competency assessments. This series of activities began with online and simultaneous competency mapping throughout Indonesia with the aim of equalizing teacher competency as a whole and divided into several aspects. This research uses critical analysis methods. Data collection techniques include document scanning, interviews, and data collection using documents. Data analysis in this research uses qualitative analysis. The results of optimizing the Sustainable Professional Development (PKB) approach for this research are as follows. (1) Assess yourself as a PAI teacher; Second, the online Competency Mapping (PK) program; the third is PAI PKB Teacher training. The results of this research show the ability of the PKB program which is expected to improve the skills and work efficiency of PAI assistants through various courses that have been successfully completed systematically and comprehensively.